The Impact of Teacher Dynamics, Spirituality, Sciences, Link & Match Concept between the Educational and Bussiness on Education Quality and Sports Excellence - Erwin Ernestus Kadar Slamet (BADAN PENERBIT STIEPARI PRESS, 2021)
This research aims to investigate the multifaceted impact of teacher dynamics, spirituality, sciences, and the link & match concept between education and business on education quality and sports excellence. The research employs a phenomenological approach to delve into the intricate connections among these variables. Sampling techniques involve purposive sampling to select participants with diverse experiences and perspectives. Data analysis is conducted through thematic analysis, allowing for the identification of key themes and patterns. Preliminary findings suggest a significant influence of teacher dynamics, spirituality, and the integration of sciences with the link & match concept on enhancing both education quality and sports excellence. These findings contribute to a deeper understanding of the holistic factors shaping educational outcomes and athletic achievements.